A novel bud mutant of navel orange (Citrus sinensis) shows tolerance to chlorosis in acidic and magnesium-deficient soils - Chaudhry, Ahmad Hassan; Hussain, Syed Bilal; Du, Wei; Liu, Yongzhong; Peng, Shu-Ang; Deng, Xiuxin; Pan, Zhiyong (Plant physiology and biochemistry, 2023)
Interveinal chlorosis in old leaves is a common occurrence in citrus orchards in southern China. The present study investigates the ‘Langfeng’ navel orange (LF, Citrus sinensis) grafted onto a Trifoliate orange (TO, Poncirus trifoliata) rootstock, which exhibits healthy green leaves, and the ‘Newhall’ navel orange (NHE, C. sinensis) grafted onto TO, which has typical magnesium (Mg) deficiency-induced chlorosis. Chemical analysis of the rhizosphere soil revealed that the pH values were around 3.92 and that both Mg and calcium (Ca) were significantly deficient in the rhizosphere soil of both grafting combinations (LF/TO and NHE/TO). Furthermore, the chlorotic leaves of NHE/TO had significantly lower levels of Mg, Ca, and phosphorus (P), and the green leaves of NHE/TO had significantly lower levels of Mg and Ca compared to the green leaves of the LF/TO. This suggests that Mg deficiency may be the primary cause of chlorosis in NHE/TO. A greenhouse study using the same graft combinations showed that the LF/TO plants had better growth than the NHE/TO, possibly by promoting Mg uptake and/or improving Mg distribution to leaves, thereby increasing carbon dioxide (CO2) assimilation and photosynthesis, optimizing carbohydrate distribution, and increasing plant biomass. This results in a phenotype that is tolerant to Mg deficiency. In conclusion, these findings suggest that the LF navel orange could be utilized in the development of new citrus varieties with improved Mg-use efficiency. •Interveinal chlorosis is common in southern China citrus orchards.•Study compares “Langfeng” navel orange (LF) on Trifoliate orange rootstock (TO) to “Newhall” navel orange (NHE) on TO.•Soil analysis showed Mg and Ca deficiencies and NHE/TO had lower levels of Mg, Ca, and P in chlorotic leaves.•Greenhouse study showed better growth in LF/TO plants, indicating improved Mg uptake and tolerance to Mg deficiency.•Findings suggest LF navel orange can be used in new citrus varieties with improved Mg-use efficiency.